Role of complement anaphylatoxin receptors in a mouse model of acute burn-induced pain. (February 2018) - Morgan, Michael; Deuis, Jennifer R.; Woodruff, Trent M.; Lewis, Richard J.; Vetter, Irina
Highlights: C3aR, C5aR1 and C5aR2 have a limited role in burn-induced pain in mice. C5aR2 mediates burn-induced edema in male mice only. Inhibiting C3aR, C5aR1 or C5aR2 is unlikely to be analgesic in burn-induced pain. Abstract: The complement system is an essential component of the innate immune response. The anaphylatoxins C3a and C5a are key drivers of the complement system, acting through the receptors C3aR, C5aR1 and C5aR2 to regulate inflammation. While a role for C5a activation of C5aR1 in inflammatory and neuropathic pain has been established, the role of the complement system in burn-induced pain has not been investigated. To address this gap, we assessed the role of complement receptors C3aR, C5aR1 and C5aR2 in a mouse model of acute burn-induced pain. Superficial burn injury was induced in C57BL/6 mice by firm application of left hind paw plantar surface to a hot plate set at 52.5 °C for 25 s. Development of burn-induced mechanical allodynia, thermal allodynia, weight bearing changes and edema was assessed in C3aR −/−, C5aR1 −/− and C5aR2 −/− mice and compared to their wild type controls over three days. Burn-induced mechanical allodynia, thermal allodynia and weight bearing changes developed normally C3aR −/−, C5aR1 −/− and C5aR2 −/− mice. However, burn-induced edema was significantly reduced in C5aR2 −/− male mice, but not C5aR2 −/− female mice. These results suggest that the complement system has a limited role in the development of acute burn-induced pain.